2017
DOI: 10.1080/01443615.2017.1352568
|View full text |Cite
|
Sign up to set email alerts
|

Is the presence of corpus callosum predictable in the first trimester?

Abstract: Corpus callosum agenesis (CCA) is a clinical condition accompanied by various aneuploidy and genetic syndromes. We identified the development of the corpus callosum (CC) in 278 patients before 18 weeks of gestational age by visualising the pericallosal artery (PCA) in the callosal sulcus and changes in the lengths and ratios of the midbrain (MB) and falx (F), which suggested elevation of the third ventricle and thalamus due to CCA in the first trimester. We succeeded in visualising the path of the PCA in 273 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…3 Furthermore, acquisition of a midsagittal view of the fetal brain is relatively easy in the first trimester of pregnancy because it represents the imaging plane used to measure the NT. Assessment of the PCA with high‐definition color Doppler represent another feasible and reproducible approach to indirectly detect CC in the first trimester of pregnancy and may help in more accurately describing the fetal anatomy in those cases with suspicion of fetal structural or chromosomal anomalies, or to reassure parents with a prior pregnancy complicated by fetal ACC 4–8,21,22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Furthermore, acquisition of a midsagittal view of the fetal brain is relatively easy in the first trimester of pregnancy because it represents the imaging plane used to measure the NT. Assessment of the PCA with high‐definition color Doppler represent another feasible and reproducible approach to indirectly detect CC in the first trimester of pregnancy and may help in more accurately describing the fetal anatomy in those cases with suspicion of fetal structural or chromosomal anomalies, or to reassure parents with a prior pregnancy complicated by fetal ACC 4–8,21,22 …”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies reported that the prenatal diagnosis of ACC can be suspected at 11–14 weeks of gestation by identifying an abnormal course of the PCA. However, the small sample size of these studies, differences in type and time at ultrasound assessment as well as the inclusion criteria impair our ability to extrapolate robust evidence on the actual diagnostic performance of first trimester ultrasound in detecting CC abnormalities in the first trimester of pregnancy 4–8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for an earlier diagnosis was undertaken and included the assessment of the visualization of the pericallosal artery (Diaz-Guerrero et al, 2013;Kalayci et al, 2018) and of the midbrain and flax diameters as potential early markers of ACC (Kalayci et al, 2018;Lachmann et al, 2013). However, a premature diagnosis of partial ACC was cautioned given the rate of misdiagnosis and the subsequent psychological burden (Min, et al 2020).…”
Section: The Prenatal Diagnosismentioning
confidence: 99%
“…14 mainly related to the corpus callosum and only showed indirect signs reflecting its presence or absence. Lachman et al[23] use the ratio midbrain and falx diameter, Pati et al[24] use the visualization and measurement of the pericallosal artery, and Kalayci et al[25] use a combination of both methods for indirect diagnosis of an absent corpus callosum.The current study demonstrates the feasibility of displaying the sagittal section of the third ventricle, fcsp, roof/cvi, commissural ▶ Fig.6cvi prediction interval (cavum veli interpositi ap/ccmm).▶ Fig.7csp prediction interval (cavum septum pellucidum ap/ccmm).…”
mentioning
confidence: 99%